2014
DOI: 10.1210/en.2013-1919
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast Growth Factor-2 Isoform (Low Molecular Weight/18 kDa) Overexpression in Preosteoblast Cells Promotes Bone Regeneration in Critical Size Calvarial Defects in Male Mice

Abstract: Repair of bone defects remains a significant clinical problem. Bone morphogenetic protein 2 (BMP2) is US Food and Drug Administration-approved for fracture healing but is expensive and has associated morbidity. Studies have shown that targeted overexpression of the 18-kDa low-molecular-weight fibroblast growth factor 2 isoform (LMW) by the osteoblastic lineage of transgenic mice increased bone mass. This study tested the hypotheses that overexpression of LMW would directly enhance healing of a critical size ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 41 publications
1
26
0
Order By: Relevance
“…A synergistic effect of FGF‐2 and BMP‐2 has been suggested by several experimental studies (Charles et al., ; Gronowicz et al., ; Su et al., ; Xiao et al., ). As previously mentioned, adding FGF‐2 might allow to reduce the dose of BMP‐2, thus reducing the risk of the negative side effects associated to a high dosage of this growth factor, and would promote hMSCs proliferation and osteogenic differentiation (Akita, Fukui, Nakagawa, Fujii & Akino, ).…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations
“…A synergistic effect of FGF‐2 and BMP‐2 has been suggested by several experimental studies (Charles et al., ; Gronowicz et al., ; Su et al., ; Xiao et al., ). As previously mentioned, adding FGF‐2 might allow to reduce the dose of BMP‐2, thus reducing the risk of the negative side effects associated to a high dosage of this growth factor, and would promote hMSCs proliferation and osteogenic differentiation (Akita, Fukui, Nakagawa, Fujii & Akino, ).…”
Section: Resultsmentioning
confidence: 89%
“…Some pre‐clinical studies have shown that combining BMP‐2 with other growth factors (Charles, Woodman, Ueno, Gronowicz & Hurley, ; Gronowicz, Jacobs, Peng, Zhu & Hurley, ; Jo, Jeong, Shin, Kang & Kim, ; Su, Xu, Sun, Gong & Zhao, ; Xiao, Ueno, Catros, Homer‐Bouthiette & Charles, ) would allow to reduce the amount of BMP‐2 delivered, thus reducing the associated side effects, such as ectopic bone formation, osteoclast activation, long‐lasting oedema formation, as well as erythema in the vicinity of the site of implantation and inappropriate adipogenesis (James, LaChaud, Shen, Asatrian & Nguyen, ; Zara, Siu, Zhang, Shen & Ngo, ), while maintaining positive regenerative outcomes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact evidence exists that FGF‐2 LMW and not FGF‐2 HMW favors bone regeneration, as FGF‐2 LMW knockout leads to decreases in mineralized bone density (Xiao et al., ), whereas FGF‐2 HMW knockout benefits bone and phosphate homeostasis in vivo (Homer‐Buthiette, Doetschman, Xiao, & Hurley, ). Moreover, overexpression of FGF‐2 LMW increases bone mass by enhanced osteoblast activity (Xiao et al., ). Apart from its positive effects on bone maintenance, FGF‐2 LMW was also reported to promote inflammation and support oxidative stress in atherosclerosis (Liang, Wang, Ma, Yan, & Yang, ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to angiogenic effects, VEGF and FGF-2 possess stimulatory effects on osteogenic differentiation of MSCs; hence VEGF and FGF-2 accelerate bone defect healing. 66,[84][85][86][87] Besides influencing the HIF-1a signaling pathway, DFO can also activate the Wnt/b-Catenin signaling pathway, enhancing osteogenic differentiation of MSCs. 40,41 This phenomenon is confirmed by our ALP and AR staining, and upregulated mRNA expression levels of Runx-2 and osteocalcin.…”
Section: Discussionmentioning
confidence: 99%